Diagnostic possibilities in peritonsillar abscess and the significance of transcutaneous ultrasound - Systematic Review of the Literature - Martyna Martyna Krasuska; Karolina Nowak; Zuzanna Olejarz; Zuzanna Drygała; Julia Wyrwał; Zuzanna Zielińska; Magdalena Słowik; Karolina Nowak; Maria Nieć; Katarzyna Gierlach (Journal of Education, Health and Sport, 2024)
Introduction and purpose: